2021
DOI: 10.1002/hbe2.247
|View full text |Cite
|
Sign up to set email alerts
|

Use of passive sensing to quantify adolescent mobile device usage: Feasibility, acceptability, and preliminary validation of the eMoodie application

Abstract: Utilizing the built‐in features of smartphones, a novel app “eMoodie” (http://www.emoodie.com) was developed which passively collects information on app and smartphone/tablet usage including duration and time of use. Youth in the US and UK participated in piloting and validating eMoodie. In the first study, we evaluated the feasibility and acceptability of eMoodie in a sample of 23 parent–child dyads (N = 46), with children ages 10–12 years. Children downloaded eMoodie onto their device, which collected inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
13
0
3
Order By: Relevance
“…Some studies have theorized that knowledge of tracking of activity on a mobile device alone likely influences the behavior of research participants [24]. Consistent with this, studies using accelerometer data for physical activity [25] and smartphone use in youth [22] show differences in participant engagement during monitoring, although the real-world significance of these changes may be minimal [22]. Furthermore, a recent meta-analysis suggested that these methods can still more accurately inform correlates of screen use, purportedly doing so more accurately than participant report alone [13], making them a valuable contribution to scientific methodology.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Some studies have theorized that knowledge of tracking of activity on a mobile device alone likely influences the behavior of research participants [24]. Consistent with this, studies using accelerometer data for physical activity [25] and smartphone use in youth [22] show differences in participant engagement during monitoring, although the real-world significance of these changes may be minimal [22]. Furthermore, a recent meta-analysis suggested that these methods can still more accurately inform correlates of screen use, purportedly doing so more accurately than participant report alone [13], making them a valuable contribution to scientific methodology.…”
Section: Introductionmentioning
confidence: 92%
“…To date, data from objective assessment methods have been primarily limited to adults and older adolescents [ 16 , 17 ], parents of children [ 18 ], and young children [ 19 ], despite many children owning smartphones beginning in midchildhood [ 20 , 21 ]. Notably, a recent study in older children (aged 10-14 years) found passive monitoring combined with ecological momentary assessment (EMA) notifications to be feasible and acceptable [ 22 ]. However, the app used by Domoff et al [ 22 ] did not calculate exact app use, leaving a gap in the literature regarding which types of apps are most commonly used among children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 ESM allows for a detailed assessment of the interaction between real-world context and phenomena that is unaffected by issues of recall. 30 Data will be collected using a mobile phone app called eMoodie, 31 which was developed specifically for young people. The ESM study will run alongside the cross-sectional and longitudinal studies sharing the same aims and with the additional aim to determine whether young people use similar personal and social resources for short-term recovery (within hours or days) as for long-term recovery (over 1 year).…”
Section: Cross-sectional and Longitudinal Cohort Studiesmentioning
confidence: 99%